2019
DOI: 10.15446/abc.v24n2.71512
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Venom: New Promise in the Treatment of Cancer

Abstract: Cancer is a public health problem due to its high worldwide morbimortality. Current treatment protocols do not guarantee complete remission, which has prompted to search for new and more effective antitumoral compounds. Several substances exhibiting cytostatic and cytotoxic effects over cancer cells might contribute to the treatment of this pathology. Some studies indicate the presence of such substances in scorpion venom. In this review, we report characteristics of the principal scorpion venom components fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…Such enhanced activity of drug-loaded phytosomes compared with the pure drug have previously been reported with QRT, and could be due to improved intracellular bioavailability [ 47 ]. In addition, the incorporation of SV into the novel formulation has also contributed to the improved cytotoxicity of QRT [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such enhanced activity of drug-loaded phytosomes compared with the pure drug have previously been reported with QRT, and could be due to improved intracellular bioavailability [ 47 ]. In addition, the incorporation of SV into the novel formulation has also contributed to the improved cytotoxicity of QRT [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also exhibited the advantage of being able to penetrate deep into tumor tissue [217,218]. Since the discovery of CTx, the list of scorpion crude venoms and isolated toxins with anticancer activity has been growing rapidly, hence a comprehensive review of all reported compounds exceeds the scope of this review, but can be found elsewhere [216][217][218][219]. Here, we present a few cherry-picked recent studies with the most significant findings.…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…CTx was the first scorpion-derived agent that demonstrated inhibitory effects on glioma cell migration and invasion. It also exhibited the advantage of being able to penetrate deep into tumor tissue [217,218]. Since the discovery of CTx, the list of scorpion crude venoms and isolated toxins with anticancer activity has been growing rapidly, hence a comprehensive review of all reported compounds exceeds the scope of this review, but can be found elsewhere [216][217][218][219].…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…that possess significant anticancer potential [14]. SV peptides have been previously reported to induce apoptosis, inhibit proliferation, angiogenesis, metastasis, and immunomodulatory effect in different types of cancers [14]. However, peptides suffer from the limitation of adequate stability, thermal degradation, fast metabolism, and a very short half-life [15].…”
Section: Introductionmentioning
confidence: 99%